Study of Ammonia Gas Emission from Broiler Houses and the Effects of Temperature, Humidity and Age on It - M Baghani (Ferdowsi University of Mashhad, 2018)
Introduction Iran as one of the largest producers of poultry in Asia and plays major role in feeding the world's population, particularly in the poultry industry. Research about this industry will help to improve the quality and the quantity of products. Increasing of the concentration of toxic gases such as NH3 (ammonia), CO2 (carbon dioxide), SH2 and CH4 in poultry houses comes from bird activity inside the barn is one of the basic problems of the farming. Increasing the amount of these gases more than standard level would cause heavy mortality and reductions in the production. Ammonia is one of the most toxic gases in poultry houses, which must be controlled. Different studies have been carried out on measurement of ammonia emissions from poultry houses to reduce energy consumption and reduce emissions of ammonia. But no specific study has been found on ammonia emissions in Iran and there is no reliable documents of ammonia emissions from poultry in this country.